ANALISIS KELAYAKAN USAHATANI TEMBAKAU (Nicotiana Tabacum) - Dinar; Dinarul Haq, Adisty; Andayani, Sri Ayu (Journal of Innovation and Research in Agriculture, 2025)
Tobacco is a commodity with considerable development potential, as evidenced by the significant foreign exchange and excise revenues generated from tobacco. Therefore, the purpose of this study was to determine the characteristics of tobacco farming in Cisalak Village, Lemahsugih District, Majalengka Regency, as well as to determine the cost structure, revenue, profit, and feasibility of the farming business. The research method used a survey technique with a quantitative descriptive approach. Thirty respondents were recruited using a purposive sampling technique. The analysis technique used was descriptive analysis, calculating fixed costs, variable costs, revenue, R/C Ratio and B/C Ratio. The results of this study indicate that running a tobacco farm requires a total fixed cost of IDR 2,100,000, a variable cost of IDR 10,000,000 and depreciation cost of IDR 1,671,000. Profit is IDR 30,000,000, and farm income is IDR 16,229,000. The feasibility analysis of this tobacco farm yields R/C Ratio and B/C Ratio of 2,18 and 1,18, indicating that this farm is feasible to continue. Keywords: Tobacco Farming, Income, Financial Feasibility.